1976
DOI: 10.1111/j.1365-2621.1976.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Muscle Cooked From the Frozen State at Low Temperature

Abstract: Top round roasts (1.35 kg) were oven roasted (OR, 94"(Z), cooked in oven film bags (OFB, 94°C) or in a slow cooker (SC, SYC) to 60" or 7O"C, or cooked in OFB or in SC 10 hr. Total cooking losses and palatability of meat and related objective measurements were similar for all cooking methods. OFB and SC roasts cooked in less (P < 0.05) time and appeared more well-done (P < 0.05) than OR roasts cooked to the same end point. Heat penetration was slower when the meat's internal temperature was below 0°C than when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Funk et al (1966) reported total cooking losses of 12.5% (deck oven) and 15.2% (convection oven) when roasts were cooked at 149C to an internal endpoint of 52C. Vollmar et al (1976) reported cooking losses of 20.8% for 2.4 kg top round roasts cooked in a moist system at 93.3C to an internal endpoint of 60C. At 149C, Ferger et al (1972) observed a 26.4% (dry) or 26.2% (moist) cooking loss from rib roasts cooked to 70C.…”
Section: Resultsmentioning
confidence: 99%
“…Funk et al (1966) reported total cooking losses of 12.5% (deck oven) and 15.2% (convection oven) when roasts were cooked at 149C to an internal endpoint of 52C. Vollmar et al (1976) reported cooking losses of 20.8% for 2.4 kg top round roasts cooked in a moist system at 93.3C to an internal endpoint of 60C. At 149C, Ferger et al (1972) observed a 26.4% (dry) or 26.2% (moist) cooking loss from rib roasts cooked to 70C.…”
Section: Resultsmentioning
confidence: 99%
“…184 ' 185 In a study evaluating both steaks and roasts, data for cooking time and internal temperature were consistent with previous work. 186 Vollmar et al 187 observed a significant increase in cooking time when beef roasts were heated from 60 to 70° C. All steaks and roasts cooked to 80° C took a longer time than those cooked to 70° C (Table 8). Interestingly, the difference in time for the steaks averaged 37% between 70 and 80° C, whereas that time difference in roasts was only approximately 15%.…”
Section: / Internal Temperaturementioning
confidence: 93%
“…Investigations of quality of food prepared in slow-cookers have been concerned with casserole-type appliances (Sundberg and Carlin, 1976;Engler and Bowers, 1975;Vollmar, Harrison, and Hogg, 1976). However, a portable oven-broiler with a slow-heat setting was introduced to the appliance market early in 1976.…”
Section: Introductionmentioning
confidence: 99%